Pyhän Mechtildin ilmestykset - Kauko, Mikko (Tietolipas, 2022)
Mechthild of Hackeborn represents medieval mysticism. Her Revelations were written down in the 1290s in Helfta, Germany. The oldest surviving versions are in Latin, but in the Middle Ages, the Revelations were translated at least into Dutch, English, Swedish, and German. The text was translated into Swedish in 1469 by Jöns Budde, a Bridgettine brother from Naantali. Budde made few omissions but many additions in the text, mainly explanations to meet the needs of the Bridgettine sisters. Budde's translation is faithful to the original text, and he made few mistakes. My Finnish translation of the text follows Budde's version where possible. However, Budde translated an abridged version that omitted some chapters, and the only surviving copy of Budde's translation is incomplete. I have therefore translated the missing sections from Latin and incorporated them in the text. My translation also includes editorial comments on the language, the contents, and the historical and theological contexts of the Revelations.